144 HYPERMETHYLATION SILENCES WNT INHIBITORY FACTOR 1 IN NASOPHARYNGEAL CARCINOMA. (1st January 2006) - Thung, E. G.; Chou, J.; You, L.; Xu, Z.; Jablons, D. M.
Abstract : Nasopharyngeal carcinoma (NPC) is an epithelial tumor that is endemic to southern China. Although much is known about its pathology and its association with Epstein-Barr virus infection, the molecular events that lead to the formation of the tumor are not clearly understood. Recently, it was discovered that the up-regulation of the wingless-type (Wnt) signaling pathway may contribute to the pathogenesis of NPC. Wnt inhibitory factor-1 (WIF-1) is an antagonist of Wnt; studies have shown that WIF-1 down-regulation and the subsequent up-regulation of Wnt signaling are found in several human cancers. In order to determine if the down-regulation of WIF-1 plays a role in NPC, the expression of human WIF-1 in NPC cells was first assessed using reverse transcription-PCR. The NPC cell lines used were CNE, HNE-1, and HONE-1. The methylation status of WIF-1 was then determined by sequencing and by using methylation-specific PCR on bisulfite-treated NPC DNA. We find that WIF-1 is not expressed in NPC cells and that CpG island hypermethylation is seen in the promoter region of WIF-1, suggesting that hypermethylation silences WIF-1 expression. These results indicate that the up-regulation of the Wnt pathway due to the methylation silencing of WIF-1 is part of the mechanism that leads to tumor formation in NPC. Discovering ways to either inhibit the Wnt pathway or remove the hypermethylation of WIF-1 can thus be potentially used to therapeutically treat NPC in patients.